Laparoscopic cholecystectomy in pregnant women can be performed safely with cesarean section (Annals of Medical Research, 2021)
Aim: The aim of this study is to demonstrate the efficacy of laparoscopic cholecystectomy performed during cesarean section in patients with symptomatic or complicated gallstones during pregnancy to prevent complications associated with gallstones in the early postpartum period.Materials and Methods: Patients were selected among the patients who were followed up in the obstetrics clinic between 2010 and 2015, who had gallbladder stones and showed symptoms such as acute cholecystitis, biliary pancreatitis, choledocholithiasis and biliary colic. Fifteen patients accepted our recommendation of laparoscopic cholecystectomy with cesarean section. Patients were evaluated together with general surgery clinic. Patients with biliary colic due to bile sludge and who underwent cholecystectomy during pregnancy were excluded from the study. Informed consent forms were obtained from the patients. The study was approved by the “Aksaray University Rectorate Human Research Ethics Committee” with the protocol number 2020/08-03.Results: Laparoscopic cholecystectomy was performed in the second trimester of pregnancy (two patients due to acute cholecystitis and one patient due to biliary pancreatitis) in three patients who did not respond to medical treatment. The other 12 patients underwent laparoscopic cholecystectomy simultaneously with cesarean section. Eight patients were discharged on postoperative first day and four patients were discharged on postoperative second day.Conclusion: We believe that laparoscopic cholecystectomy can be performed safely with caesarean section in pregnant women with symptomatic and complicated gallstones.
Keywords: Cholecystectomy; cholelithiasis; laparoscopy; pregnancy